Whatever Speculation. Issue 1 (7th November 2019) - Slager, Henk
MaHKUscript's 2019 issue Whatever Speculation will focus on a key-concept in the history of artistic thinking, i.e. speculation. Nowadays speculation has been devalued to a mere one-dimensional, economic meaning. It seems that speculative thought about both future forms of knowledge and solutions to problems surrounding existence and social viability has made way for an almost self-evident resignation in the present moment and the status quo, producing a blurred view of complex issues that characterize the here and now. For that reason it is extremely urgent to reconsider different and alternative connotations of speculation and bring them up to date.